Design and development of instant linear gel for coal bed methane gas operations - R. V. V. Ramana Murthy; K. S. R. Murthy; Murthy Chavali (PT Mattawang Mediatama Solution, 2021)
Linear gel fracturing fluids are expressed with an extensive range of materials/polymers in an aqueous base. Earlier we developed fracturing linear gel with fossil diesel, bio-diesel and also used suspending anti-settling agents and emulsifiers. Here we report on a novel and an efficient method for the preparation of linear gel direct mix with water, guar gum and sodium acetate together instantly. In this research work, we used water instead of diesel without any need to mix anti-settling agents, suspending agents, emulsifiers that resulted in 30 viscosity linear gel. The degradation pattern observed from the breaker test showed that a reduction in gel viscosity depends on time, temperature & breaker concentration. Ammonium per sulphate or Ammonium per oxidisulphate and enzyme-G were used for oxidation purpose to break the gel gradually at a particular static temperature. Observations from experiments revealed that a small concentration of breaker provides rapid break compared to oxidative breakers. This article, designing of fracturing fluids describes how to use the fluid's viscosity generated by the gelling agents like guar gum for CBM operations.